Estimated displaced products and ratios of distillers' co-products from corn ethanol plants and the implications of lifecycle analysis. Issue 6 (November 2010) - Arora, Salil; Wu, May; Wang, Michael
Displacement of conventional animal feed components – corn, soybean meal and urea – by distillers' co-products has been revisited. We developed the distillers' co-products displacement ratios at different levels: the feedlot level, the US market level and the composite US and export market level, in order to provide a relevant estimate for ethanol plant operators, stakeholders and decision makers. As expected, corn is still the single largest component in the conventional beef cattle diet to be displaced by distillers' co-products, followed by soybean meal. On average, 1 kg of wet distillers' grains could displace 1.313 kg of corn and urea together, when it is used as a substitute in the diet of beef cattle; for distillers' dried grain with solubles, 1.271 kg of corn and urea can be displaced per kg of distillers' dried grain with solubles fed to beef cattle. Uncertainties about the consistency of reported data, export market and emerging new co-products are discussed. In addition, the use of distillers' co-products as an animal feed may have an indirect impact on the lifecycle assessment of corn ethanol.